APPLICATION OF PhET SIMULATION TO ELECTRICAL CIRCUITS MATERIAL IN ONLINE LEARNING - Nufus Choirum Masruroh; Amelya Vivianti; Putri Maulida Anggraeni; Siti Nailil Waroh; Nur Wakhidah (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
This study aims to determine the application of learning electrical materials online using the PhET (Physics Education and Technology) simulation media for grade VI students. This quantitative descriptive study illustrates how the PhET simulation media is used in learning to cognitive learning outcomes. Sampling using purposive sampling technique as many as 10 students of MIN 2 Sidoarjo. Data collection techniques were carried out using questionnaires and tests which were sent to students via google form. The student's score is compared to the school's KKM score and the percentage is calculated. The results showed that (i) 80% of students scored above 75 with an average of 85,4 and (ii) 91% of students responded positively to using this application.